Pulsão de saber : uma leitura na obra freudiana - Mikowski, Esther Maynart Pereira (2015)
This study´s theme is the drive to know (Die Wissentrieb) the impulse to research questions about sex and his own existence, presented by Freud on Three Essays on The Theory of Sexuality. The main objective were recapture Freudian texts to sustain our hypotheses of operational concept in his work. The literature review in Chapter I around education and clinic pointed out to main studies directions on infantile sexuality, drive theory, transfer and culture. In Chapter II, treating key texts on infantile sexuality and infantile sexual theories, Little Hans´ case became representative for research and theories engaged on his curiosity. In Chapter III we did a brief review in the Freudian drive theory in its two moments. Finally, Chapter IV is about knowledge production in the culture and the clinic management that were proposed as drive to know destiny. We found both in the late Freudian texts about culture and religion and in the articles about psychoanalytic technique the investigative character presented by subject. Therefore, we understand psychoanalysis proves a subject to know in the clinic and in the culture what makes drive to know operative on Freudian work.